Polarization in reporting the 2019 presidential election campaign on Indonesian television - Budi Utami; Deddy Mulyana; Eni Maryani; Dadang Rahmat Hidayat (Cogent Social Sciences)
Qualitative research conducted on the 2019 Presidential Election in Indonesia focused on analyzing the coverage of Kompas TV, a national news television station unaffiliated with any political party. This study utilized a systematic approach following Creswell and Creswell’s (2018) six-stage qualitative data analysis. Kompas TV news regarding presidential candidates Joko Widodo and Prabowo Subianto during the campaign period was scrutinized. The data preparation involved collecting and reviewing campaign news scripts and broadcasts. Coding was applied using Dan Nimmo’s propaganda techniques to discern patterns and themes in coverage. The analysis revealed that glittering generalities, emphasizing positive attributes without criticizing opponents, dominated Kompas TV’s coverage, constituting 49.23% of the campaign news. The study inferred that Kompas TV tended to use words and phrases to promote virtue, while avoiding negativity towards any party or individual. Kompas TV tends to be careful and chooses not to use bad labels on ideas, people, goals, or objects to influence the audience to reject them. As a news media known to be neutral, Kompas TV tries to maintain an objective image and balance when conducting propaganda. Glittering generalities (49.23%), using good words to describe something to obtain support, plain folks (26.15%), portraying candidates as ordinary people, and transfers (18.46%), associating positive traits with candidates, were the most prevalent propaganda techniques employed.